Preparation of TiO2 Nanotubes Loaded on Polyurethane Membrane and Research on Their Photocatalytic Properties - Longli Lin; Qijun Wu; Xun Gong; Yu Zhang (Journal of Analytical Methods in Chemistry)
To solve the problem of separation and recovery of photocatalyst in water, the modification of TiO2 was studied as well as its immobilization and photocatalytic properties. To improve surface properties, TiO2 nanotubes were synthesized by a hydrothermal method and silylated by silane coupling agents to introduce a certain functional group. Supported on polyurethane (PU) membrane, TiO2 nanotubes were prepared to produce immobilized PU/TiO2. Catalysts were characterized and identified by means of Fourier-transform infrared spectroscopy (FTIR), attenuated total reflectance Fourier-transform infrared spectroscopy (ATR-FTIR), and scanning electron microscopy (SEM). Results showed that silylated TiO2 nanotubes were well grafted on the surface of the activated PU membrane. With a 300 W high pressure mercury lamp as light source, the photocatalytic activity and stability of immobilized PU/TiO2 were investigated with degrading methyl orange. It was showed that the target is degraded by immobilized PU/TiO2 with high activation and the catalytic performance is stable for a long time if catalyst is washed with ethanol.